Susceptibility of shigellae to mecillinam, nalidixic acid, trimethoprim, and five other antimicrobial agents. - Hansson, H B (1981)
A total of 199 strains of shigella (1 Shigella dysenteriae, 15 S. boydii, 47 S. flexneri, and 136 S. sonnei) isolated in Malmö, Sweden, within a 3-year period (1977 through January 1980) were tested with the agar plate dilution method for susceptibility to commonly used and newer antimicrobial agents. Mecillinam, nalidixic acid, and trimethoprim had the best in vitro activity. S. flexneri dominated among strains resistant to three or more antimicrobial agents and were less susceptible to ampicillin, chloramphenicol, and doxycycline than other types studied. Sixty-four percent of the strains were resistant to sulfamethoxazole. In vitro, a synergistic effect with trimethoprim was shown only in strains susceptible to sulfamethoxazole. The amidinopenicillin mecillinam was highly active against shigellae. When resistance occurred, it was linked to ampicillin in 17 of 18 strains. The quinolines, here represented by nalidixic acid, might be the drugs of choice.